Pengaruh model pembelajaran inkuiri berbantuan media kubus magic terhadap pemahaman konsep materi FPB dan KPK - Aprillyani Rohmana; Indiati Indiati; Tria Mardiana (Universitas Muhammadiyah Magelang, 2021)
This study aims to determine the effect of the inquiry learning model assisted by the magic cube media on understanding the concept of FPB and KPK material for IV grade students in Kalisari Village, Tempuran District, Magelang Regency. This type of research is using experimental research with a research design â€œOne Group Pretest Posttestâ€. The subjects of this study were 15 IV grade students in the Village of Kalisari, Tempuran Subdistrict as the experimental class. The sampling technique used was saturated sampling technique. The data collection technique used a test in the form of multiple choice questions. The data analysis used was the Paired Sample T Test with the help of the SPSS version 24 application program for windows. The conclusion of this study snows that the inquiry learning model assisted by the magic cube media has an effect on the concept of understanding the FPB and KPK material for IV grade students in Kalisari Village, Tempuran Subdistrict. This is proven by the results of the Paired Sample T Test analysis 0,000 < 0,05.